A Study of Caputo-Hadamard-Type Fractional Differential Equations with Nonlocal Boundary Conditions - Wafa Shammakh (Journal of Function Spaces)
Existence and uniqueness results of positive solutions to nonlinear boundary value problems for Caputo-Hadamard fractional differential equations by using some fixed point theorems are presented. The related Green’s function for the boundary value problem is given, and some useful properties of Green’s function are obtained. Example is presented to illustrate the main results.